Biochar Suppresses Growth, Pupation and Eclosion Success of a Specialist (Manduca sexta) and a Generalist (Spodoptera frugiperda) Insect Herbivore - Nischal Wagle; Soumya Unnikrishnan; Satinderpal Kaur; Engil Pereira; Rupesh Kariyat (Journal of Sustainable Agriculture and Environment)
ABSTRACT Biochar is a charcoal‐like substance made by the pyrolysis of organic material from agricultural and forestry waste. While biochar is well documented for altering soil physicochemical conditions, few studies have investigated its possible effects on the management of arthropod pests. Tobacco hornworm (Manduca sexta) and fall armyworm (Spodoptera frugiperda, FAW) are specialist and generalist insect herbivores respectively, that can cause significant defoliation in natural and agricultural ecosystems. In this study, we examined whether walnut shell biochar can affect growth and development of these herbivores. Specifically, we investigated how biochar influences parameters such as mass gain, length of pupation, pupal mass, pupal volume, deformity, duration of eclosion, wingspan, body length, thorax mass and survival. Laboratory experiments were conducted by allowing caterpillars to feed on a modified artificial diet and pupate in a pupation medium mixed with biochar. This was followed by allowing the insects to complete pupation and eclose. We found that in the generalist pest FAW, caterpillars feeding on biochar treated diet gained significantly lower mass and had lower pupal volume compared to their conspecifics feeding on normal control diet. Our results also show that biochar treatment on M. sexta pupae led to a reduction in pupal mass, and increased pupal deformity compared to the control, and these negative effects cascaded to significant reduction in adult mass. We also found that adult wingspan, body length, and survival were significantly lower in the biochar treatment when compared to the control for both species. In addition, the biochar treatments also prolonged the time to eclosion of adult moths and decreased their overall survivability. Based on these findings, we conclude that biochar negatively impacts the growth, pupation and eclosion of lepidopteran herbivores, indicating its potential use in sustainable pest management strategies.